Effectiveness of myocardial dysfunction pharmacological correction in children with congenital heart disease after surgical treatment - Dudnyk, V. M.; Zborowskay, O. O. (Journal of Education, Health and Sport, 2015)
Dudnyk V. M., Zborowskay O. O. Ефективність фармакологічної корекції міокардіальної дисфункції у дітей з вродженими вадами серця після оперативного лікування = Effectiveness of myocardial dysfunction pharmacological correction in children with congenital heart disease after surgical treatment. Journal of Education, Health and Sport. 2015;5(4):117-128. ISSN 2391-8306. DOI: 10.5281/zenodo.16665 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A117-128 https://pbn.nauka.gov.pl/works/553516 http://dx.doi.org/10.5281/zenodo.16665 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.03.2015. Accepted: 27.03.2015. УДК 616.248 – 053:611.018.74:616 – 008.6 ЕФЕКТИВНІСТЬ ФАРМАКОЛОГІЧНОЇ КОРЕКЦІЇ МІОКАРДІАЛЬНОЇ ДИСФУНКЦІЇ У ДІТЕЙ З ВРОДЖЕНИМИ ВАДАМИ СЕРЦЯ ПІСЛЯ ОПЕРАТИВНОГО ЛІКУВАННЯ EFFECTIVENESS OF MYOCARDIAL DYSFUNCTION PHARMACOLOGICAL CORRECTION IN CHILDREN WITH CONGENITAL HEART DISEASE AFTER SURGICAL TREATMENT В. М. Дудник, О. О. Зборовська V. M. Dudnyk, O. O. Zborowskay Вінницький національний медичний університет ім.М.І.Пирогова Vinnitsa National Medical University, Vinnytsya Abstract Background. Among children with congenital heart disease (CHD) undergoing cardiac surgery the incidence of heart failure (HF) is 61.4%. The main goal in myocardial dysfunction medication is to create conditions for adequate cardiac output (afterload) and a decrease in the volume filling chambers of the heart (preload). The study of metabolic reactions in the myocardium by pathological conditions increases the interest in drugs that are endogenous regulators of energy metabolism. The aim of our study was to evaluate the effectiveness of myocardial dysfunction pharmacological correction in children with congenital heart disease after surgical treatment. Materials and methods. We examined 184 child from the CHD, which was made radical correction of anatomical defects aged 1 month to 18 years (mean age 9,42 ± 3,43 years). CHD belonged to different hemodynamic types, namely 119 children (64,67 ± 3,52%) had a bug with the enrichment of the pulmonary circulation (EPC); 35 children (19,02 ± 2,89%) - with the depletion of the EPC and 30 children (16,00 ± 2,72%) - CHD depletion of systemic circulation. Children with every type CHD were divided into two groups, representative by age, sex, postoperative experience. In the study group in addition to the basic treatment of heart failure children receiving therapy with Ahvantar (oral 100 mg / kg per day, 30 days). All children performed echocardiography examination using tissue doplerohraifiyi to assess longitudinal wall motion of the left and right ventricles of the heart in different phases cycle. Results and discussion. Children with primary research group had significantly better clinical dynamics than those of the comparison group, namely for all types of BBC incidence of heart failure symptoms in children of the main group decreased in 2,14-5,00 times. Adding to the treatment regimen of L-carnitine in children of the main group was accompanied by improved contractile parameters of left ventricular performance and S`mshp S` microns to 16,17-35,91%, and the right amplitude TAPSE and S` maybe 17,31- 21.71%. Joining kardiometabolitnoyi therapy to the basic treatment of heart failure in children and the CHD core group of blood circulation in the IWC mainly improved diastolic function of the right ventricle in terms of E / E`tk to 17,88-31,64%, while the Air Force of the depletion reduced the systemic circulation values of E / E`mshp and E / E`mk to 23.80% and 47.41%, respectively, which significantly differed from those of the comparison group received after treatment. Conclusion. Correction of myocardial dysfunction in children with BBC after surgical correction requires a differentiated approach, depending on the type of hemodynamic disorders in a large and a small circle of blood circulation. Keywords: congenital heart defect, children, myocardial dysfunction, treatment. Реферат Актуальність проблеми. Серед дітей з вродженими вадами серця (ВВС), що перенесли кардіохірургічне втручання частота виникнення серцевої недостатності (СН) становить 61,4 %. Головною метою в медикаментозному лікуванні міокардіальної дисфункції є створення умов для адекватного серцевого викиду (постнавантаження) та зменшенням об’ємного наповнення камер серця (переднавантаження). Дослідження обмінних реакцій в міокарді за патологічних умов підвищує інтерес до препаратів, що є ендогенними регуляторами енергетичного обміну. Метою нашого дослідження було оцінити ефективність фармакологічної корекції міокардіальної дисфункції у дітей з вродженими вадами серця після оперативного лікування. Матеріали та методи. Нами обстежено 184 дитини з ВВС, котрим була виконана радикальна корекція анатомічних дефектів у віці від 1 місяця до 18 років (середній вік 9,42±3,43 років). ВВС відносились до різних гемодинамічних типів, а саме 119 дітей (64,67±3,52 %) мали ваду із збагаченням малого кола кровообігу (МКК); 35 дітей (19,02±2,89 %) – із збідненням МКК та 30 дітей (16,00±2,72%) – ВВС із збідненням системного кола кровообігу. Діти з кожним типом ВВС поділялись на дві групи, репрезентативні за віком, статтю, післяопераційним стажем. В основній групі крім базисної терапії СН діти отримували кардіометаболітну терапію препаратом Агвантар (перорально 100 мг/кг на добу, 30 днів.) Усім дітям проводили ЕХО-КГ обстеження з використанням тканинної доплерограіфії для оцінки поздовжнього руху стінок лівого і правого шлуночків в різні фази серцевого циклу. Результати та їх обговорення. Діти із основної групи дослідження мали достовірно кращу клінічну динаміку, ніж діти з групи порівняння, а саме при всіх типах ВВС частота виникнення симптомів СН у дітей основної групи знизилась в 2,14-5,00 рази. Додавання до схеми лікування L-карнітину у дітей основної групи супроводжувалось покращенням показників скоротливої функції лівого шлуночку за показниками S`мшп та S` мкна 16,17-35,91 %, а правого за амплітудою TAPSE та S` тк17,31-21,71 %. Приєднання кардіометаболітної терапії до базисного лікування СН у дітей основної групи та ВВС із порушенням кровообігу в МКК переважно покращувало діастолічну функцію правого шлуночку за показником E/Е`тк на 17,88-31,64 %, а при ВВС із збідненням системного кола кровообігу знижувало значення E/Е`мшп таE/Е`мк на 23,80 % та 47,41 %, відповідно, що достовірно відрізняло їх від показників групи порівняння отриманими після лікування. Висновок. Корекція міокардіальної дисфункції у дітей з ВВС після оперативної корекції потребує диференційованого підходу, залежно від типу гемодинамічних порушень по великому та малому колу кровообігу. Ключові слова: вроджена вада серця, діти, міокардіальна дисфункція, лікування.